Religious minorities and their impact on Iraqi social peace - الياسري, حسين قاسم محمد (Al-Adab Journal, 2019)
This research deals with the religious minorities in Iraq (Christianity, Yezidi and Sabean Mandaean) and their impact on social peace negatively or positively and in harmony with the Muslim majority. The research also discusses the history and geographic presence of these minorities, the human rights violations, And the rights achieved under the new Iraq and its aspirations to obtain more rights, and extrapolation to the future, and the main output of the research is that these minorities lived in harmony with the majority did not witness a state of conflict and civil wars with each other, but their rights have been violated by the Systems that ruled Iraq, and control Daesh on areas where minorities, as well as its exposure to the displacement and murder after 2003, and that the lack of social security and stability in their regions will lead to external interference, which will reflect negatively on the national and social security .